Strategic issues of raising international financing - A. A. Tarasov (Вестник университета)
The article discusses some strategic issues related to the raising of international financing by the means of syndicated loans and eurobonds by Russian corporations. Author proposes a method for benchmarking the financial position of the company compared to its competitors. This analysis uses key performance indicators, including the debtfinancing share, credit rating, weighted average cost of capital. Crises have become a frequent occurrence in global economy. For the top-managers of the corporation, one of the key tasks during the period of economic uncertainty is the handling of communications with lenders and investors for the control of the company’s financial position. The article considers the specifics of providing the required information about company activity during the crisis. The key document is the financial model, based on the macroeconomic, industrial, and operational assumptions regarding the borrower’s operations. Using financial covenants as an example, we consider the mechanics of incorporating changes into the current loan terms, as well as the raising of new funding by using shirt-term revolving credit facilities. For the solution of one of the key strategic goals of corporate finance – execution of mergers and acquisitions transactions – we present an algorithm of raising financing by using syndicated loans and eurobonds.